2016
DOI: 10.1039/c6ra19418d
|View full text |Cite
|
Sign up to set email alerts
|

3C–SiC on glass: an ideal platform for temperature sensors under visible light illumination

Abstract: This letter reports on cubic silicon carbide (3C–SiC) transferred on a glass substrate as an ideal platform for thermoresistive sensors which can be used for in situ temperature measurement during optical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…4,5 Hence, the cost of a wafer is reduced signicantly and, most importantly, 3C-SiC is compatible with conventional N/MEMS technologies. 6,7 The proper metallization of any device is very important to obtain exact and accurate responses. However, the metallization of MEMS devices generally requires multiple timeconsuming processes (i.e., lithography and metal etching), expensive metal sources (e.g., Au, Ni, Al, and Ti), and specialized equipment, such as sputters and electron beam evaporators.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Hence, the cost of a wafer is reduced signicantly and, most importantly, 3C-SiC is compatible with conventional N/MEMS technologies. 6,7 The proper metallization of any device is very important to obtain exact and accurate responses. However, the metallization of MEMS devices generally requires multiple timeconsuming processes (i.e., lithography and metal etching), expensive metal sources (e.g., Au, Ni, Al, and Ti), and specialized equipment, such as sputters and electron beam evaporators.…”
Section: Introductionmentioning
confidence: 99%
“…In order to gain insight into this phenomenon, we transferred the 3C-SiC thin-lm from Si to glass substrate using the FIB (Focused Ion Beam) technique (details of transferring process have been reported in 24 ). It was observed that the resistance of the transferred 3C-SiC thin lm remained almost constant under dierent illumination intensities (635 nm), reecting that due to the large band gap, 3C-SiC is insensitive to the applied illumination (See supporting information, Figure S4).…”
mentioning
confidence: 99%
“…To demonstrate the sensitivity enhancement in the proposed structure, we developed piezoresistive Subsequently, arrays of SiC nanowires were fabricated using focused ion beam with Ga + ions [26,27]. Finally, the Si membrane was formed by etching the Si substrates from the backside.…”
Section: Characterization Of Nanowires Based Pressure Sensorsmentioning
confidence: 99%